Report of a preventive intervention based on cognitive-behavioural therapy and positive psychology for adolescent athletes - Marques Strey, A.; Lindern, D.; Lisboa, C. S. D. M. (Journal of Human Sport & Exercise, 2019)
This study aimed to report the experience of a group intervention, with a preventive focus on anxiety and maladaptive behaviours and aimed at improving social and coping skills and at promoting well-being for soccer athletes from basic categories. Eight sessions of intervention were performed, each lasting 90 minutes, structured in the Cognitive-behavioural Therapy model and with weekly frequency. The results indicate that the athletes had a high level of achievement of the meetings that aimed at psychoeducation and practiced management skills of anxiety, social skills and cognitive distortions.